Simple Additive Weigthing (SAW) Untuk Pemberian Reward Kepada Karyawan Pada PT. CAHAYA KASIH ANUGRAH - Fernando B Siahaan (JSAI (Journal Scientific and Applied Informatics), 2020)
Reward is a form of appreciation given by the company to its employees for the achievements given in a certain period, this gift is a form of motivation to all employees to show their performance at the company. The problem is that there is no system for conducting an assessment because it is still manual, a decision support system is needed to determine employee performance appraisals based on criteria set by the company. Simple additive weighting is the best method to perform weighted summation of the performance rating of each alternative on the attribute. The purpose of this study was to determine the assessment of the criteria for the best employees to receive rewards using simple additive weighting. In the discussion, it is explained that the criteria for evaluating employee performance consist of competence, responsibility, behavior, cooperation and discipline. The conclusion is that the best employees are Brother Fredy's after adding the preference values of each leader, namely 1.46, 1.53 and 1.58 with a total value of 4.57, this assessment follows the criteria set by the company for all its employees.